Digital Documentary Photography of Ecotourism : A Case Study of the Belum Temenggor Rainforest Complex - Hashim, Khairul Hazrin (2010)
The focus of this study is to understand the relationship between photography and ecotourism. Its objective is to establish a generic framework for digital documentary photography of ecotourism. The phenomena of digital photography have taken people by storm since the last decade and it has reverberated inquiries on the application of photography, both as a recording tool and medium of expression. These questions revolve around technology, fundamental principles of methods, techniques, and its processes from the photographer\'s side as well as the subjects, issues, and events to be photographed.